1998
DOI: 10.1007/s002130050485
|View full text |Cite
|
Sign up to set email alerts
|

Personality related effects of nicotine, mode of application, and expectancies on performance, emotional states, and desire for smoking

Abstract: Three separate factors relevant to nicotine effects have been investigated in this experiment in combination: the experimentally induced expectation about receiving a sham or a nicotine cigarette, the mode of application of nicotine by a tablet, by a cigarette or not at all, while the belief of receiving the nicotine via smoking was held constant in each condition (by nicotine or sham smoking), and the personality factors of extraversion or neuroticism, respectively. Ninety-six healthy female student smokers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…Assuming that uncomfortably high biochemical stress responses are reduced by the sedating effects of ethanol [31][32][33], and perhaps nicotine, highly emotional WKR should consume more of these 2 substances, which they indeed do. Similarly, higher anxiety scores of the WKR should also predict higher ethanol [14,[34][35][36][37] and perhaps nicotine consumption [37], which again was found to be so. In rats bred selectively for their stress responses we found that rats with high plasma catecholamine stress responses consumed more ethanol than did rats with low plasma catecholamine responses whereas both lines did not differ in their cocaine preference [38].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that uncomfortably high biochemical stress responses are reduced by the sedating effects of ethanol [31][32][33], and perhaps nicotine, highly emotional WKR should consume more of these 2 substances, which they indeed do. Similarly, higher anxiety scores of the WKR should also predict higher ethanol [14,[34][35][36][37] and perhaps nicotine consumption [37], which again was found to be so. In rats bred selectively for their stress responses we found that rats with high plasma catecholamine stress responses consumed more ethanol than did rats with low plasma catecholamine responses whereas both lines did not differ in their cocaine preference [38].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the negative mood changes may be caused by nicotine itself (Breslau et al, 1998;Parrott, 1999). Perkins et al (1994) found that, compared with placebo, nicotine increased tension, even in smokers, and Netter et al (1998) found that smoking increased feelings of arousal and emotional tension in female smokers and increased ratings of anxiety and sadness in those with higher neuroticism scores. On cessation of smoking, after the first week of abstinence, ex-smokers report better mood and lower anxiety than when they had been smoking (Hughes et al, 1990;West and Hajek, 1997).…”
Section: Nicotinementioning
confidence: 97%
“…To our knowledge, only one other lab study used the balanced-placebo design with cigarettes (Netter, Hennig, Huwe, & Olbrich, 1998), but other features of this study make it difficult to interpret main or interaction effects of nicotine and instructions. Specifically, in addition to assignment of subjects to nicotine and denicotinized research cigarettes (made by Philip Morris, Inc.), this study included random assignment to nicotine or inactive tablets, but all subjects were told the tablet was not nicotine.…”
Section: Placebo Smoking Researchmentioning
confidence: 97%